Comparative study between flow cytometric and conventional HPE method in multinodular goiter- USM experience - Othman, Nor Hayati (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2009)
In HUSM, the most common thyroid diseases is multinodular goiter (MNG). In an earlier study of 300 consecutive cases it was noted that malignant transformation of MNG in our population was high, 36.8%; higher that what is cited in the literature. We postulated that MNG is a precursor lesion to the development of malignant thyroid diseases. The current study is an extension of the previous work - is to determine if flow cytometry could be used to diagnose early malignant transformation among patients who came in with MNG using the theoretical premise that flow cytometry detects DNA changes in abnormal cells. Progress in defining ·the role of flow cytometry in the assessment of solid tumors has been slow, partly because of the greater histological complexity of solid tissues, and partly because of practical difficulties in obtaining suitable material compared to hematological diseases. Over the past decade, great advances have been made and flow cytometry is now used more frequently for measurement of DNA content in solid tumors. Recently, the technique has been extended by the development of fl.ow cytometric assays for other cellular components, such as membrane markers, oncoprotein and growth factor receptors. There can be little doubt that it will become a valuable technique in the study of the biology and treatment of cancer. Quantitative multiparameter flow cytometric analysis of surface antigen and DNA has become a well established and reliable technique in the investigation of lymphoreticular cells. In solid tumors however, flow cytometry has mainly been used for DNA analysis, and more recently for quantitative assay of nuclear antigens. Locally, no work has been done utilizing flow cytometric determination of multinodular goiter using single cell suspension. We embarked on diagnosing MNG using fl.ow cytometry and detect malignant transformation in thyroid cell suspension based on DNA abnormalities.